KATNISS AS A REPRESENTATION OF GIRL POWER IN HUNGER GAMES TRILOGY - Emanuela Giovanni Toisuta; Priska Febrinia Handojo (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This study is about the representation of girl power in Hunger Games trilogy.Hunger Games trilogy shows how women that are represented by the main character “Katniss”, can do what they want regardless others people opinion. It shows that Katniss as the main character lives in a society that does not have roles between man and woman by showing some action through her characterisctics in the story that against the culture and society. She is able to do anything without thinking about what man or woman should do. Thus,this thesis aims at showing girl power characteristics that are being represented by Katniss. Therefore, I will analyze girl power characteristics in Katniss by using girl power concept. Moreover through this analysis, I find that there are some girl power characteristics that are being represented by Katniss. First, she is an independent woman. Second, she is equally depends on her “brains and brawn”. Third, Katniss is a self-determined woman. For the result of the analysis, it can be concluded that Katniss is the representation of girl power that is shown through her action, words, and thoughts.